Quadratic Cost-Volume Relationship and Timing of Demand Information: A Reply. - Ijiri, Yuji; Itami, Hiroyuki (The Accounting Review, 1975)
Presents a reply to the commentary on the study on the quadratic cost-volume relationship and timing of demand information. Types of quadratic cost functions analyzed; Alternative proposed in the commentary regarding fixed costs; Failure of the study to point out the implications of the optimization analysis according to four possibilities.